2017
DOI: 10.1101/106203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic analysis of family data reveals additional genetic effects on intelligence and personality

Abstract: Pedigree-based analyses of intelligence have reported that genetic differences account for 50-80% of the phenotypic variation. For personality traits these effects are smaller, with 34-48% of the variance being explained by genetic differences. However, molecular genetic studies using unrelated individuals typically report a heritability estimate of around 30% for intelligence and between 0% and 15% for personality variables. Pedigree-based estimates and molecular genetic estimates may differ because current g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 90 publications
7
48
0
Order By: Relevance
“…Scotland revealed a large increase in heritability compared to a standard GREML analysis of unrelated individuals (Hill et al 2018). For neuroticism, the total heritability from the best-fitting model was 30%, primarily accounted for by kin-based genetic effects (19%), as well as common variant effects tagged in studies of unrelated individuals (11% -akin to SNP heritability).…”
Section: Greml-kin Analyses In Generationmentioning
confidence: 90%
See 2 more Smart Citations
“…Scotland revealed a large increase in heritability compared to a standard GREML analysis of unrelated individuals (Hill et al 2018). For neuroticism, the total heritability from the best-fitting model was 30%, primarily accounted for by kin-based genetic effects (19%), as well as common variant effects tagged in studies of unrelated individuals (11% -akin to SNP heritability).…”
Section: Greml-kin Analyses In Generationmentioning
confidence: 90%
“…Moreover, a replication of these results would suggest that most of the variance in education (86%) can be captured with measured parameters. Notably, the authors also found that rarer variants (0.1%-1% in frequency) explained 12% of the variance in education, but did not influence variation in neuroticism (Hill et al 2018).…”
Section: Greml-kin Analyses In Generationmentioning
confidence: 94%
See 1 more Smart Citation
“…Second, it is possible that similar functional processes have diverging neural signatures across samples. (Part of) variation in personality is due to rare genetic variants (Penke L and M Jokela 2016;Boyle EA et al 2017;Hill WD et al 2018) which could lead to differences between samples leading to variable patterns of brain-behavior correspondences.…”
Section: Discussionmentioning
confidence: 99%
“…Current imputation panels are limited in their ability to accurately assess variants with frequencies below 1%, but will continuously improve as imputation panels increase in size and representation of varying populations [41,42]. For example, a recent family-based study [43] has demonstrated that more than half of the variation in cognitive ability is attributable to rare variation not captured by current GWASs (see also [44]). Importantly, very little of this variation is private to individual families; most could be captured by population-based reference panels of sufficient size to accurately impute variants at 0.1% minor allele frequency and greater.…”
Section: Discussionmentioning
confidence: 99%